Possibilities of Converting Extensive Cattle Breeding to Organic Production Model in Balikesir Province - Hülya HANOĞLU ORAL; Halil İbrahim KUZ and Camal DAYANIKLI and Abdullah Taner ÖNALDI and Emre ALARSLAN and Esra DUMAN (ISPEC Journal of Agricultural Sciences, 2021)
Although intensive cattle breeding is dominant in Balıkesir province, extensive breeding is maintained via native breeds and cultural crossbreeds in some mountainous regions. Similarities between the practices performed in extensive and organic livestock systems facilitate the transition into organic system. In this study, it was aimed to determine the possibilities of transition into organic production model by examining the structural characteristics of the extensive cattle breeding maintained in the city. For this purpose, 270 neighborhoods, where extensive cattle breeding is performed, were selected according to the purposeful sampling method. The study material was composed of the data obtained via the questionnaires administered in the face-to-face interviews held with 561 cattle breeding enterprises determined in these neighborhoods in accordance with the simple random sampling method. In the enterprises, the animals are able to use pasture areas and, in 83.60% of them, they are able to reach open-air ranges. In organic agriculture, the permitted breeding methods are used; in 59.36% of the enterprises, artificial insemination is applied and, in 40.64% of them, natural mating is applied. In some regions of the districts of Marmara, Sındırgı, İvrindi and Dursunbey, where the enterprises having the native breeds and the cultural crossbreeds are concentrated, transformation of the extensive cattle breeding maintained based on rangelands into organic system seems to be easier and cheaper. However, the proprietors should be informed about the standards of organic animal production and how to keep records, which is compulsory for monitoring all the processes, and encouraged to produce organic forages, which is the basic input of organic animal breeding.